Effects of Different Modified Biochars on Growth of Kosteletzkya virginica and Corresponding Transcriptome Analysis - Hao Dai; Mingyun Jia; Jianhui Xue; Yuying Huang; Jinping Yu (Plants)
Modified biochar can effectively improve the quality and environment of coastal saline–alkali soil, but its effects on the growth and development of halophytes and its mechanism are still unclear. This study systematically evaluated the growth-promoting effects and preliminary mechanisms of H3PO4-modified biochar (HBC) and H3PO4–kaolinite–biochar composite (HBCK) on the economically important halophyte Kosteletzkya virginica. The results demonstrated that the application of HBC/HBCK significantly enhanced plant growth, resulting in increases of over 55% in plant height and greater than 100% in biomass relative to the control. Multidimensional mechanistic analysis revealed the following: (1) accumulation of nitrogen (N), phosphorus (P), and potassium (K) increased by at least 40%, significantly enhancing nutrient uptake; (2) increases in the activities of superoxide dismutase (SOD) and peroxidase (POD) by over 100% and 70%, respectively, markedly boosting antioxidant capacity and effectively alleviating oxidative stress; (3) molecular regulation via the activation of transcription factor networks (HSP, MYB, TCP, AP2/ERF, bZIP, and NLP) and modulation of key genes in ABA, BR, and JA signaling pathways (CYP707A, CYP90, and OPR2), establishing a multi-layered stress adaptation and growth promotion system. Beyond assessing the growth-promoting effects of modified biochars, this study provides novel insights into the regulatory transcription factor networks and phytohormone signaling pathways, offering theoretical foundations for the molecular design of biochars for saline–alkali soil remediation.